Phenotypic characterization of Arabidopsis thaliana lines overexpressing AVP1 and MIOX4 in response to abiotic stresses. (8th September 2020) - Nepal, Nirman; Yactayo‐Chang, Jessica P.; Gable, Ricky; Wilkie, Austin; Martin, Jazmin; Aniemena, Chineche L.; Gaxiola, Roberto; Lorence, Argelia
Abstract : Premise: AVP1 (H + ‐pyrophosphatase) and MIOX4 ( myo ‐inositol oxygenase) are genes that, when overexpressed individually, enhance the growth and abiotic stress tolerance of Arabidopsis thaliana plants. We propose that pyramiding AVP1 and MIOX4 genes will further improve stress tolerance under water‐limited and salt‐stress conditions. Methods: MIOX4 and AVP1 reciprocal crosses were developed and phenomic approaches used to investigate the possible synergy between these genes. Results: Under normal and stress conditions, the crosses had higher foliar ascorbate content than the wild‐type and parental lines. Under water‐limited conditions, the crosses also displayed an enhanced growth rate and biomass compared with the control. The observed increases in photosystem II efficiency, linear electron flow, and relative chlorophyll content may have contributed to this observed phenotype. Additionally, the crosses retained more water than the controls when subjected to salt stress. Higher seed yields were also observed in the crosses compared with the controls when grown under salt and water‐limitation stresses. Discussion: Overall, these results suggest the combinatorial effect of overexpressing MIOX4 and AVP1 may be more advantageous than the individual traits for enhancing stress tolerance and seed yields during crop improvement.